Meningkatkan Sportifitas Anak Melalui Turnamen Mini Soccer antar SD/MI - Umam, Khotibul; Sari, Ika Auliya (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2025)
This study aims to improve children's sportsmanship through healthy competition and teamwork. The methods employed were observation and administering questionnaires to participants. This study used a quasi-experimental design with a pretest-posttest approach to measure improvements in children's sportsmanship after participating in a mini-soccer tournament between elementary and Islamic elementary schools (SD/MI). The results showed an increase in sportsmanship attitudes, such as honesty, mutual respect, and emotional control. This tournament was effective as a learning medium for children's sportsmanship values. In conclusion, the mini-soccer tournament between elementary and Islamic elementary schools (SD/MI) in Jembangan Village, Banjarnegara, was effective in improving children's sportsmanship attitudes, such as honesty, mutual respect, and emotional control. In addition to being a form of entertainment, this activity also instilled positive values ​​that are important for children's character development.   Keywords: Children, Jembangan Village, Banjarnegara, Mini Soccer, Elementary and Islamic Elementary Schools (SD/MI), Sportsmanship, Tournament